Engineering and sustainability performance of self-compacting palm oil mill incinerated waste concrete - Kanadasan, J.; Razak, Hashim Abdul (Elsevier, 2015)
The different stages in the processing of palm oil generate various types of waste by-products, which have to be disposed of appropriately for a cleaner environment and to reduce pollution. In this study, palm oil clinker (POC), one of the by-products of the palm oil mill, was utilized in the production of self-compacting concrete (SCC). SCC has diverse types of structural application due to its own enhanced self-consolidating behaviour. The proportioning of the mixes was based on particle packing, which integrates both aggregate packing and void volume for a mix of aggregates. Combinations of POC and natural aggregate were studied at various substitution levels ranging from 0 to 100 for both fresh and hardened properties. In addition, a few of the results were integrated into sustainability components to evaluate the effectiveness of the concrete both economically and environmentally. It was found that POC aggregate require three times lower energy consumption for preparation compared to conventional aggregate. Overall, POC incorporation showed enhanced structural efficiency with a significant reduction in cost and energy usage. Furthermore, the sustainability of the construction industry can be conserved with the introduction of POC as an alternative source for concreting work. (C) 2014 Elsevier Ltd. All rights reserved.